Perlindungan Hukum Bagi Konsumen Atas Kerugian Akibat Kelalaian Promotor dalam Penyelenggaraan Konser Musik Ditinjau Dari Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Estefania Bernarda Irrina Miguel Bano; Darius Mauritsisus; Rini Marselin Kaesmetan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Negligence of promoters in organizing music concerts can cause losses to consumers as occurred in the exchange of e-tickets for the SEVENTEEN "Right Here" World Tour in Jakarta concert by PT Melania Citra Permata (Mecimapro) on February 4, 2025 at Lotte Mall Jakarta, which resulted in queues, inconvenience, and physical injury to consumers. This study aims to analyze the form of legal protection for consumers based on Law Number 8 of 1999 concerning Consumer Protection and the promoter’s legal responsibility for the losses incurred. This study uses a normative legal research method with a statutory approach and a conceptual approach, which is analyzed descriptively qualitatively through literature studies. The results of the study indicate that Mecimapro has violated its preventive protection obligations because it failed to provide an orderly and safe ticket exchange system, while repressive efforts in the form of an apology and amicable settlement have not fulfilled the provisions for compensation as stipulated in Article 19 of the Consumer Protection Law. Legally, Mecimapro’s actions can be classified as a breach of contract under Article 1239 of the Civil Code and an unlawful act under Article 1365 of the Civil Code. Therefore, the promoter, as a business actor, is obligated to provide legal protection and compensation to consumers for any losses they experience.